(untitled) (International Journal of Environmental Sciences, 2025)
This article presents a viewpoint on the mathematical modeling of polysemantic units that belong to the lexical-semantic category of "spirituality"; the modeling method makes use of the theory of sets and the property of elements. The objective, rationale, and usefulness of using mathematical techniques to language have all been proven. This model discusses the formal formulation of language systems and their analysis using statistical and mathematical techniques. The approach outlines some things to think about regarding language norms and structure, as well as a more thorough examination of how they are used. A thorough examination and formal definition of polysemantic lexemes are part of the modeling process, which takes into consideration the language’s phonological, grammatical, semantic, and pragmatic features.